Algoritma Genetika pada Optimasi Persoalan Knapsack 0/1 - Abdullah Husein; Dewi Murni; Meira Parma Dewi (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – The problem of 0/1 Knapsack is an issue in the selection of objects from the set of objects that each object have a decision